Health-related quality of life of HIV-infected children in Uyo. Akwa Ibom State, Nigeria - Megbelayin, Fadekemi Folasade; Akpan, Mkpouto Udeme; Dixon-Umo, Ofonime (International Journal of Research in Medical Sciences, 2023)
Background: HIV-infected children are surviving into adolescence and adulthood due to the effectiveness of highly active antiretroviral therapy (HAART) but they now have to cope with living with a chronic disease. Health-related quality of life (HRQOL) has been shown to be an invaluable tool in assessing health outcome in chronic health conditions including HIV. Little is known about the HRQOL of HIV-infected children in both developing and developed countries. The study aimed at assessing the HRQOL of Nigerian children with HIV infection and compare it with that of healthy children in Uyo. Methods: A cross-sectional study of 211 HIV-infected children aged 2 to 15 years and 211 age, sex and social class-matched HIV-uninfected children with their caregivers was conducted at the University of Uyo Teaching Hospital, Uyo for a duration of nine months from October 2016 to July 2017. A generic version of the Pediatric Quality of Life Inventory (PedsQL 4.0) was used to measure their HRQOL. Results: From both self and proxy reports, there was no significant difference in the mean total HRQOL score of HIV-infected children and that of HIV-uninfected children. Conclusions: HRQOL of HIV-infected children in Uyo, Akwa Ibom state was good and comparable to that of HIV-uninfected children. Assessment of HRQOL should be incorporated into routine antiretroviral therapy ART programmes as a measure of the outcome of disease management. This will further help to identify needs and direct interventions for holistic care of these vulnerable children.